Oil and Gas Production Wastewater: Soil Contamination and Pollution Prevention - John Pichtel (Applied and Environmental Soil Science)
During oil and natural gas production, so-called “produced water” comprises the largest byproduct stream. In addition, many oil and gas operations are augmented via injection of hydraulic fracturing (HF) fluids into the formation. Both produced water and HF fluids may contain hundreds of individual chemicals, some known to be detrimental to public health and the environment. Oil and gas production wastewater may serve a range of beneficial purposes, particularly in arid regions, if managed correctly. Numerous treatment technologies have been developed that allow for injection, discharge to the land surface, or beneficial reuse. Although many papers have addressed the effects of oil and gas production wastewater (OGPW) on groundwater and surface water quality, significantly less information is available on the effects of these fluids on the soil resource. This review paper compiles fundamental information on numerous chemicals used and produced during oil and gas development and their effects on the soil environment. Additionally, pollution prevention technologies relating to OGPW are presented. An understanding of the effects of OGPW on soil chemical, physical, and biological properties can provide a foundation for effective remediation of OGPW-affected soils; additionally, sustainable reuse of oil and gas water for irrigation and industrial purposes may be enhanced.